Study of the interaction between mannitol and nucleosides using fluorescent probe - Shchodryi, V.B.; Kachkovskyi, O.D.; Slominskyi, Yu.L.; Shaudyk, Ye.O.; Tkachuk, Ze.Yu. (Reports of the National Academy of Sciences of Ukraine, 2017)
We have studied the interaction of ribonucleosides (RN) with mannitol using a fluorescent probe. It is established that, during of the test dye titration with increasing concentrations of solutions of RN and the complex of RN with mannitol (RNM), a decrease of the intensity of fluorescence of a dye solution is observed. The drop of the fluorescence intensity of the RNM complex is less in comparison to the solution of RN. A difference in spectral characteristics of RN and the complex of RNM with a test dye is shown. These results may indicate the interaction of mannitol with nitrogenous base. Interaction between mannitol and nucleoside occurs probably with the formation of hydrogen bonds between two parallel O–H groups of mannitol and generating centers of hydrogen bonds in the heterocycles of nucleosides.